Study of Social Behavior in Sheep - Habibi, Emal (Journal of Natural Sciences – Kabul University, 2023)
This article examines various social behaviors in sheep, including seasonal breeding, libido, courtship and mating behaviors, pre-parturient ewe behaviors, ewe behavior during and after lambing, post-parturient lamb behaviors, feeding behaviors, and behaviors during sickness and health. Sheep are defenseless animals whose primary protection against predators is fleeing. They display strong social bonds and a tendency to follow a leader, particularly during movement and grazing. Understanding these behaviors is crucial for sheep farmers, as such knowledge minimizes harm to both the animals and their owners. This article reviews the social behaviors of sheep, emphasizing their significance in farming practices.